Pathogenic E. coli in the Food Chain across the Arab Countries: A Descriptive Review - Mohamed-Yousif Ibrahim Mohamed; Ihab Habib (Foods, 2023)
Foodborne bacterial infections caused by pathogens are a widespread problem in the Middle East, leading to significant economic losses and negative impacts on public health. This review aims to offer insights into the recent literature regarding the occurrence of harmful E. coli bacteria in the food supply of Arab countries. Additionally, it aims to summarize existing information on health issues and the state of resistance to antibiotics. The reviewed evidence highlights a lack of a comprehensive understanding of the extent to which harmful E. coli genes are present in the food supply of Arab countries. Efforts to identify the source of harmful E. coli in the Arab world through molecular characterization are limited. The Gulf Cooperation Council (GCC) countries have conducted few surveys specifically targeting harmful E. coli in the food supply. Despite having qualitative data that indicate the presence or absence of harmful E. coli, there is a noticeable absence of quantitative data regarding the actual numbers of harmful E. coli in chicken meat supplies across all Arab countries. While reports about harmful E. coli in animal-derived foods are common, especially in North African Arab countries, the literature emphasized in this review underscores the ongoing challenge that harmful E. coli pose to food safety and public health in Arab countries.